Implementation of Salibu Rice Cultivation Technology in Percut Sei Tuan Sub-District - Mayly, Syarifa; Syafri, A (Journal of Saintech Transfer, 2018)
Percut Sei Tuan Sub-district is an agricultural production center in Deli Serdang Regency. The area of irrigated paddy field in Percut Sei Tuan Sub-district comprises of 3,610 ha and 1,616 ha of non-irrigated paddy field. The farmer association groups (tani mitra) consisting of Farmer Group "Pasar II" and Farmer Group "Mulia" are located in Tanjung Selamat Village. Much land in Tanjung Selamat Village has been converted into an industrial area; previously the paddy field area reached 600 hectares, but only 200 hectares remains now. The Farmer Groups "Pasar II" and "Mulia" consist of 30 and 76 farmers with paddy rice field area of 25 ha and 23 ha respectively, and rice productivity amounts to 6.2 tons/ha and 7 tons/ha. The problems of the farmers were the high land use conversion resulting in reduced harvested area and only a few farmers change the local location-specific organic materials into organic fertilizers independently. The purposes of this community service activity were to increase the farmers' income through the implementation of salibu technology whereby farmers can harvest 2-3 times in one planting and to increase the farmers’ understanding and knowledge about the manufacturing process of organic fertilizer and pesticide. The solutions offered were including counseling, a training and plot demonstration on salibu technology, and the production of bokashi straw. The outcome of this IbM has resulted in several things: bokashi of compressed hay with Local Microorganism from cattle intestine and Trichoderma, organic pesticide products based on Corynebacterium and Trichoderma, and farming analysis with salibu technology.